Alteration of the Intestinal Bacterial Community in Rainbow Trout (Oncorhynchus mykiss): The Role of Animal, Plant, and Microbial Diets - Aleksandra S. Chervochkina; Nadezhda O. Pastukhova; Andrey S. Aksenov (Microbiology Research)
Intestinal bacterial community in rainbow trout (Oncorhynchus mykiss) is increasingly recognized as important for aquaculture and fish health. This review summarizes the current knowledge on how various feed components, including animal- and plant-derived ingredients, as well as other feed additives, influence the gut microbiota of rainbow trout. Studies using 16S rRNA gene profiling and metagenomics demonstrate how dietary changes affect the composition, diversity, and functionality of bacterial communities. The findings suggest that there is no single optimal alternative ingredient for fish feeds, but emphasize that the ratio of natural components plays a more significant role in shaping the intestinal bacterial community of trout. This balance is crucial for maintaining diversity, functionality, and overall fish health, thereby promoting growth and disease resistance, while enhancing aquaculture efficiency. The use of popular animal protein derived from the larva of Hermetia illucens increases the amount of Pseudomonadota, but the chitin they contain can prevent the absorption of nutrients. Thus, the development of optimal feed formulas requires careful selection and balancing of various natural ingredients to sustain a healthy microbiota and overall fish well-being.